NSUN6-mediated 5-methylcytosine modification of NDRG1 mRNA promotes radioresistance in cervical cancer - Yu, Min; Ni, Mengdong; Xu, Fei; Liu, Chaohua; Chen, Lihua; Li, Jiana; Xia, Siyu; Diao, Yixin; Chen, Jiaxin; Zhu, Jun; Wu, Xiaohua; Tang, Min; et al. (Molecular cancer, 2024)
Radioresistance is the leading cause of death in advanced cervical cancer (CC). Dysregulation of RNA modification has recently emerged as a regulatory mechanism in radiation and drug resistance. We aimed to explore the biological function and clinical significance of 5-methylcytosine (m C) in cervical cancer radiosensitivity. The abundance of RNA modification in radiotherapy-resistant and sensitive CC specimens was quantified by liquid chromatography-tandem mass spectrometry. The essential RNA modification-related genes involved in CC radiosensitivity were screened via RNA sequencing. The effect of NSUN6 on radiosensitivity was verified in CC cell lines, cell-derived xenograft (CDX), and 3D bioprinted patient-derived organoid (PDO). The mechanisms of NSUN6 in regulating CC radiosensitivity were investigated by integrative m C sequencing, mRNA sequencing, and RNA immunoprecipitation. We found a higher abundance of m C modification in resistant CC samples, and NSUN6 was the essential m C-regulating gene concerning radiosensitivity. NSUN6 overexpression was clinically correlated with radioresistance and poor prognosis in cervical cancer. Functionally, higher NSUN6 expression was associated with radioresistance in the 3D PDO model of cervical cancer. Moreover, silencing NSUN6 increased CC radiosensitivity in vivo and in vitro. Mechanistically, NDRG1 was one of the downstream target genes of NSUN6 identified by integrated m C-seq, mRNA-seq, and functional validation. NSUN6 promoted the m C modification of NDRG1 mRNA, and the m C reader ALYREF bound explicitly to the m C-labeled NDRG1 mRNA and enhanced NDRG1 mRNA stability. NDRG1 overexpression promoted homologous recombination-mediated DNA repair, which in turn led to radioresistance in cervical cancer. Aberrant m C hypermethylation and NSUN6 overexpression drive resistance to radiotherapy in cervical cancer. Elevated NSUN6 expression promotes radioresistance in cervical cancer by activating the NSUN6/ALYREF-m C-NDRG1 pathway. The low expression of NSUN6 in cervical cancer indicates sensitivity to radiotherapy and a better prognosis.